Genotype phenotype correlation of cadasil patients-single center experience - Han Cebi, Alper; Boz, Cavit (Annals of Medical Research, 2021)
Aim: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is the most common inherited form of cerebral small-vessel disease. The gene that causes CADASIL is the NOTCH3 gene located on the 19th chromosome. The prevalence of the disease which can present with many different neurological and psychiatric symptoms is higher than detected. We wanted to increase awareness of this disease with our publication.Materials and Methods: Total of 20 people, 12 males and 8 females, between the ages of 26-64 were included in our study. Age of onset, initial symptoms and diagnostic processes were evaluated. Results: The most common initial symptoms of the patients were muscle weakness. In addition, there were symptoms of sensory loss and headache. Although it was rare, there was also a history of seizures and behavioral disorders. Depending on these symptoms, patients were mostly followed up with a long-term Multiple Sclerosis pre-diagnosis.Conclusion: CADASIL is a genetic disease that presents symptoms with very different clinical findings and is more common than expected. The genetic disorder that causes the disease can be diagnosed faster with new technologies. With family screening, asymptomatic individuals can be screened and early awareness can be created. Also the transmission of the disease to the next generations can be prevented.
Keywords: CADASIL; early diagnosis; genotype; NOTCH3; phenotype